2017
DOI: 10.1002/pds.4200
|View full text |Cite
|
Sign up to set email alerts
|

The burden and management of cytochrome P450 2D6 (CYP2D6)‐mediated drug–drug interaction (DDI): co‐medication of metoprolol and paroxetine or fluoxetine in the elderly

Abstract: Despite the signalling software, metoprolol-paroxetine/fluoxetine combinations are still observed in the elderly population. The clinical impact of these interactions needs further investigation. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 60 publications
(72 reference statements)
3
27
0
Order By: Relevance
“…Bahar et al reported that among all co‐prescriptions of beta‐blockers with paroxetine/fluoxetine during 1994–2014 for elderly patients in the community pharmacies in the Netherlands, 52% of them was metoprolol‐paroxetine/fluoxetine combination. The numbers of other beta‐blockers combined with paroxetine/fluoxetine were 17%, 12% and 19% for atenolol, bisoprolol and any other beta‐blockers respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Bahar et al reported that among all co‐prescriptions of beta‐blockers with paroxetine/fluoxetine during 1994–2014 for elderly patients in the community pharmacies in the Netherlands, 52% of them was metoprolol‐paroxetine/fluoxetine combination. The numbers of other beta‐blockers combined with paroxetine/fluoxetine were 17%, 12% and 19% for atenolol, bisoprolol and any other beta‐blockers respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other clinical settings, in psychiatric practice, DDIs present a serious, constantly increasing clinical problem, especially in older patients. Previous studies identified DDIs in psychiatric hospitalization but focused on antidepressants (Markowitz & Devine, ) and drugs with action on cytochrome P450 (CYP) 2D6 and 3A4 (Bahar et al., ; Davies, Eayrs, Pratt, & Lennard, ), as well as inpatients in General Hospitals and psychiatric units (Sinclair et al., ). These studies did not analyse DDI in view of nursing care of psychiatric patients, considering the impact on patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, despite the fact that computerized DDI alerting systems have been incorporated in the electronic prescription systems and applied before the dispensing process in the pharmacy, the combination of metoprolol‐paroxetine/fluoxetine is still common in older patients . One possible reason is that there is a conflicting response of the applied surveillance systems in assessing the DDI because of the contrasting evidence in the clinical consequences of metoprolol and paroxetine/fluoxetine interaction . The G‐standard, a product from the “Royal Dutch Association for the Advancement of Pharmacy” (KNMP) and used by approximately 45% of the pharmacies, does alert the interaction, but the Pharmabase, a product from the Health Base Foundation and used by approximately 55% of the pharmacies, has been stopping alerting the combination since 2005 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically relevant cytochrome P450 mediated drug‐drug interactions (DDI) are prevalent in geriatric patients with multiple comorbidities such as cardiovascular and psychiatric diseases . Metoprolol and paroxetine/fluoxetine as the drugs of choice for treating these chronic illnesses consecutively are often observed to be co‐prescribed in the elderly . Several studies have reported that the combination triggers cytochrome P450 2D6 (CYP2D6) mediated pharmacokinetic DDI .…”
Section: Introductionmentioning
confidence: 99%